DE pedagogy courses: overcoming challenges - constructing innovations - Andréia Morés (Universidade Federal de Santa Maria, 2014)
The current research was carried out at the University of Caxias do Sul (UCS) and the Federal University of Rio Grande do Sul (UFRGS) with the objective of investigating the technologic, scientific and pedagogic innovations presented in the Pedagogy courses in the Distance Education (DE) mode of these Universities. The adopted method for the qualitative investigation of this research was the Case Study, as defined by Yin (2005). The theoretical foundation that supported the research comprised studies presented by the Brazilian Association of Distance Education, Belloni (2003), Santos (2008) and Leite (2005) and Audy (2006), among others. The study revealed that one is on the way to the construction of DE practices with innovating approaches since both DE Pedagogy courses introduce technologic, scientific and pedagogic innovations that prompt a new way of knowing, teaching and learning at the university.